Compete or rest?: Willingness to compete hurt among adolescent elite athletes - Mayer, Jochen; Giel, Katrin Elisabeth; Malcolm, Dominic; Schneider, Sven; Diehl, Katharina; Zipfel, Stephan; Thiel, Ansgar (Psychology of sport and exercise, 2018)
Objective - Training and competing despite underlying health problems is a common social practice in sport. Adolescent elite athletes are particularly vulnerable to possible health consequences of this risky behavior due to their very sensitive developmental stage. Conceptualizing this phenomenon of playing hurt as sickness presenteeism, and taking the concept of absence/presence legitimacy into account, this paper analyzes the propensity of adolescent elite athletes to compete in the face of health problems. The central aim is to empirically identify characteristics of elite sport subcultures which affect athletes’ willingness to compete hurt (WCH). - Materials & methods - Based on a comprehensive sample of 1138 German elite adolescent athletes from all Olympic sports (14-18 years), the paper applies classification tree analysis to analyze the social and individual determinants of the WCH. - Results - Determinants on three hierarchical levels were identified, including type of sport, perceptions of social pressure, coach's leadership style and athletes' age. The group with the highest WCH were athletes from technical sports who have a coach with an autocratic leadership style. Second was athletes from ball games, and those in aesthetic and weight-dependent sports, aged between 17 and 18 years old. The lowest mean WCH-score, by some distance, occurred amongst the group of endurance and power sports athletes who experienced no direct social pressure to play hurt. - Conclusions - The findings enhance our understanding of absence/presence legitimacy in highly competitive social contexts and contribute to the development of more effective target-group-specific health prevention programs for young athletes.
Available online: 07 December 2017
Gesehen am 23.03.2020